PENYUSUNAN HOUSE OF QUALITY MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Yvette Josephine; Ahmad; Andres (Jurnal Mitra Teknik Industri, 2023)
PT. XYZ is a company that produces industrial shelf. There were several complaints such as dented racks, peeled off paint racks, uneven heights, incomplete and untidy welds, or other things that caused customer dissatisfaction. This research aims to measure the level of customer satisfaction with the company's performance in the service aspect and also the quality of the products produced. With this research, it will provide recommendations for improvements to PT. XYZ. The service quality method is used to determine the distribution of attributes based on quadrants. After the results were obtained, further questionnaires were distributed regarding product quality. Finally, it is continued with the Quality Function Deployment method for making a House of Quality and the priority technical response is obtained, namely the need to improve product quality as a top priority, the need to select and use appropriate and reliable material suppliers as the second priority, the need to pay attention to checking goods so that they are delivered properly as the third priority, it is necessary to hold training for production workers as the fourth priority. Meanwhile, based on the normalized row weight, the attributes that affect quality are the design of the shelf model, the neatness of the product in the process, the superiority of the product compared to competitors, the product reaches the customer without any defects, the product has been tested in use.